Large diameter flow meters speak volumes. Issue 1 (January 2017) - Lowrie, Richard
Abstract : The price of water is increasing all over the world. As a result, it is necessary for the water industry to have the most accurate methods of flow measurement available. This article explains how volumetric flow measuring accuracies are achieved and certified.